PENGARUH STRATEGI PEMBELAJARAN DAN RELIGIUSITAS TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA ISLAM SISWA KELAS XI SMK TELKOM SANDHY PUTRA MEDAN TAHUN AJARAN 2009/2010 - Sri Hidayati (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2016)
This research was aimed at finding out the specific and significant effect between instructional strategy and religiousity in the student’s achievement in Islamic religion. This research applied quasi eksperiment method with factorial design 2 x 2 and the technique of data analyzing used two way ANAVA at significant α = 0.05. Population of the research were 138 students who were on the second class of SMK Telkom Medan, and 76 students were chosen as sample by using cluster random sampling. Objective test and questionnaires were used to collect data both in instructional strategy (tadzkiroh and mudzakaroh strategy) and religiousity. Validity tests were found out before administering instruments. Point Biserial formula is used to find Islamic achievement test validity, and Product Moment formula is used for religiousity test validity. Reliability test for Islamic achievement used Spearman-Brown formula and for religiousity questionnaires used KR-20 formula. The result showed that there is the effect between instructional strategy and religiousity in the student’s achievement in Islamic religion.